Nursing Actions after Hip Total Joint Replacement Surgery - Petravičienė, Zita; Bartašiūnienė, Vida (Slauga. Mokslas ir praktika, 2023)
The joint replacement surgery is one of the greatest achievements of medicine these days. They are one of the most effective surgical interventions, performed recently, both in medical and economic terms [1].Every year in Lithuania as well as worldwide, the number of joint replacement surgeries is constantly increasing. This is influenced by the ageing population as well as the increasing number of people with chronic degenerative joint diseases [2].Despite the fact that hip, knee total joint replacement surgeries have become routine orthopedic surgeries, however, special care and nursing by medical employees are required during the postoperative period.The purpose of the research. To analyze nursing actions after the hip total joint replacement surgery. A quantitative survey has been performed by the questionnaire method; its participants were nurses, working in health care institutions of Utena City.The research revealed that the nurses shall assess the patient's general condition, his/her vital indicators, the wound, the drains and solve theproblems that have occurred.
Keywords: nurse; patient; function